Analisis Faktor -Faktor yang Mempengaruhi Minat dan Prestasi Belajar Siswa SD di Kabupaten Lombok Timur - Iskandar Iskandar; Muhamad Ali; Nuraini Nuraini (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to analyze the factors influencing the learning interest and academic achievement of elementary school students in East Lombok Regency. The phenomenon of low learning interest and the disparity in achievement levels among students have become significant concerns in improving the quality of basic education in the region. This research employs a qualitative approach with a descriptive research design. The population consists of all elementary school students in the Bunga Melati Cluster, while the samples were selected through purposive sampling from several schools representing the cluster. Data were collected through observation, interviews, and documentation of students' learning, followed by a data analysis of the factors affecting learning interest and achievement. The results indicate that internal factors, such as personal desire, feelings of enjoyment, attention, diligence, task completion, and discipline, have a significant influence on students' learning interest and achievement. Furthermore, external factors, including parental upbringing and the school environment, provide a substantial contribution to the improvement of learning outcomes. Simultaneously, both internal and external factors exert a strong positive influence on the learning interest and academic achievement of elementary school students in East Lombok Regency. These findings underscore the importance of synergy between schools and the family environment in creating a conducive learning atmosphere oriented toward the holistic development of students' potential